Komunikasi Antar Budaya - Abdi Fauji Hadiono (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2016)
The purpose of this study is about the origin of the area that causes dialect differences in the cottage Pesantren Darussalam Blokagung Banyuwangi. This research is field study (field research) by using qualitative research approach. While the research method that researchers use is descriptive research method, for the validity of research data. Techniques used in this data collection is to use participant observation techniques, interview techniques, and documentation techniques. Based on the theories and reality in the field can be concluded that the difference of regional origin causes dialect differences in panties Darussalam pesantren Blokagung Banyuwangi